A Review of the Macau's Judiciary Police: Opportunities and Challenges in the Wake of the 21st Century - Che, Ion Fong (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

A work report on Macao trade and investment promotion institute - Chan, Ka Un (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Aid and poverty reduction: comparing China and France's aid policies and projects in Guinea - Diakité, Ansoumane Douty (University of Saint Joseph, 2016)
The purpose of this research is to analyse the nexus between foreign aid and poverty reduction. In this research, aid provided by traditional and (re)emerging donors, China and France, was compared to understand their strategies toward poverty reduction and the impact of their aid in improving the conditions of their beneficiaries. Guinea, a Least Developed Country, was used as unit of comparison and assessment. Qualitative research methodology was used to collect data about the two aid donors, China and France. Among other research tools used, there are documents’ analysis (official documents from donors and recipients, declarations, scholarly works, media articles, etc.), interviews with various stakeholders, site visits and observation. As for main findings, this research found similarities and differences between China and France’s aid strategies in general and in Guinea in particular. There are similarities in the ways they integrate poverty reduction into their aid policies, motives and partly in their geographical and sectoral allocation systems. In terms of differences, they use different instruments and conditions to deliver their aid for poverty reduction. Regarding the impact of their aid, both donors have to some extent contributed to improving the access of the poor population in Guinea to basic services such as education, health, water and sanitation, etc. Finally, contrary to those who have denied the importance of foreign aid as a financial tool to reduce poverty, this research posits that aid is still a relevant tool to address poverty. However, more work needs to be done at donor, recipient and direct beneficiaries’ levels to ensure its effectiveness. On the other hand, it posits that the divide between traditional and (re)-emerging donors is becoming blurred as their strategies to address poverty are becoming increasingly alike
Keywords: Thesis and Dissertations PhD in Government Studies (D-GS); University of Saint Joseph

Anti-corruption policy and sunshine law coping with globalization: the declaration of assets and interests in the CCAC - Kuong, Cheok Man (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Breakthrough of self-containment: a work report of the Macao meteorological and geophysical bureau - Lee, In Tai (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Child protection during emergencies in Fiji and Tonga: enabling, constraining or controlling children's agency and participation - Stuebing, Dennis L. (University of Saint Joseph, 2017)
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph

Contributions to the Macao's Social Security Fund: the Arbitrary System - Un, Ka Man (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Corruption in Macao causes, consequences and challenges ahead - Tong, Ka Ieng (University of Saint Joseph, 2010)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Dealing with a changing society: a work report on further development of the government infnormation bureau - Loi, I. Man (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Developing Teledifusao de Macau (TDM) Issues and Prospects - Siew, Pek Leng (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Drug abuse and trafficking in Macao: a perspective on the challenges for the law enforcement - Ho, Cheng I. (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Environmental Legacy of the Genocide: An Exploration into the Contamination Potential of Mass Grave Soils in Post-Genocide Rwanda - Amuno, Solomon; Tran, Emilie (University of Saint Joseph, 2013)
Keywords: Environmental; Genocide; Legacy; Rwanda

Fashion design in Macau: the local government's role in the development of culture and creative industries - Lo, Nei Ian (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Food safety in Macao :a review of the Civic and Municipal Affairs Bureau's Food Safety Centre - Lou, Kai Yin (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Government policy coping with human resources management in the Venetian Macao Resort Hotel - Che, Man San (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Heading for success in government services: a case study on the administrative and human resouces policies of the DSI - Lei, Ming Kei (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Healthcare governance coping with globalization: a work report on the administrative policy of the CHCSJ Hospital and Macao Health Bureau - Rosario, Anabela Luiza do (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Impact Assessment of the Macao Forum's Seminars (colloquia) on the Economy and Public Policy-Making in Portuguese Speaking Countries - An Illustration of South-South Cooperation - Tran, Émilie (University of Saint Joseph, 2015)

Macao development strategy research centre: work report - He, Wenjing (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Policy Reform for Higher Education in Macao - Chan, Weng I. (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Quality assurance for Macao's higher education institutions: challenges and opportunities - Cheong, Wai San (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Road and traffic management in Macao challenges and way ahead - Lau, Kuai I. (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Social unrest in Xinjiang in the 21st century: crisis of the Chinese multinational state? - Flores, Rui (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Strategic management coping with contemporary globalization: a work report on the administrative policy of the mpi - bell centre of english - Ma, Si Ka (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Striving for success in diversities: a case study on perspective of administrative and government policy of the cultural affairs bureau - Wong, Sut Ieng (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Striving for sucess in governmental management: a work report on administration and government policy of the monetary authority of macao - Choi, Lai Si (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Sustainable innovation in the face of globalization: a work report on the policy reform of the DSAJ and its subordinate department CRCBM - Chan, San San (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The BRICS and the global order in the early XXI century - Kern, Rafaela Chemale (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The evolution and SWOT analysis of Macao's social security system - Chiang, Lidia (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The evolution of gaming legalization and junket regulation: a comparative study of Macao's and Nevada's gaming industry - Cheong, Weng Lam (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The impact of government policy on the tourism industry: a work report on strategic management of the Macao government tourist office - Sio, Ka Pek (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The Impact of Illegal Contributions on Social Security Scheme and Governance: A Work report on Strategic Management of the Social Security Fund - Cheang, Sin I. (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The impact of social support on the mental health of the visually impaired in Macao = 社會支援對於澳門視障人士的心理影響 - Loi, Wai Cheng (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The legal service of the Identification Services Bureau of Macao SAR: reforms and way ahead - Leong, Pui Man (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

The Macau Forum and China's Soft Power in the Making: Training the Elite of the Development Portuguese Speaking Countries" - Tran, Émilie; Matias, José Carlos (China - An International Journal, 2015)

The seminars of the Macao forum: An illustration of China’s soft-power diplomacy towards the Portuguese-speaking countries - Tran, Emilie; Dos Santos, Jose Carlos Matias (China: An International Journal, 2015)
This article reviews the role that the Macao Special Administrative Region (SAR) plays in China’s cultural and public diplomacy through training programmes organised by the Macao Forum and tailored for the elite of the world’s Portuguese-speaking countries (PSCs). It begins with a review of China’s approach to key instruments of its soft-power offensive and strategy towards the developing world, followed by an overview of Beijing’s linkages with each PSC. Formulated as an expression of China’s cultural diplomacy towards the PSCs, the seminars of the Macao Forum serve as a kind of cooperation in which the provider party—rather than delivering tangible goods and services such as food, money, loans or infrastructure—actually offers grey matter in the form of ideas for initiatives in public policies and reforms, in order to foster further economic development and administrative rationalisation. Adding to an intense debate and substantial literature that discuss quantitatively and qualitatively China’s role in and aid provision to Africa, the authors argue that China, through the Macao Forum’s training programmes, courts the developing PSCs by building the capacity of their human capital, targeting in particular those in the public and private sectors who are in a position to implement their ideas.

Work report - Chan, Kai Iong (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Work Report: the Venetian Macao resort hotel - Lei, Iok Kei (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph